Hotel v Krkonoších - Polák, Tomáš (Vysoké učení technické v Brně. Fakulta stavební, 2018)
Diplomová práce řeší projekt novostavby hotelu v Krkonoších. Diplomová práce je zpracována ve formě projektové dokumentace pro provedení stavby. Stavba je umístěná v obci Špindlerův Mlýn ve svažitém terénu. Objekt je navržen z obousměrného stěnového systému porotherm a stropy jsou navrženy jako skládané také ze systému porotherm. Stavba je obdélníkového půdorysu se sedlovou střechou s vikýři. Krytina střechy je navržena z tašek pálených Tondach a konstrukce je navržena z dřevěných prvků. Obvodové stěny podzemního podlaží budou z betonových tvarovek BS Klatovy. Vnitřní schodiště bude železobetonové. Výtahová šachta přes všechna podlaží bude opatřena evakuačním výtahem. Objekt bude zateplen certifikovaným zateplovacím systémem ETICS.

This master´s thesis proposes a design for a new hotel in the Giant. This master´s thesis is elaborated in the form of project documentation for construction. The building is located in the village Spindleruv Mlyn in sloping terrain. The object is designed from a two-way wall system, the porotherm, and the ceilings are designed as stacked also from the porotherm system. The building is a rectangular ground plan with a saddle roof and a dormer. Roof cover is designed from Tondach-baked bags and design is made of wooden elements. The perimeter walls of the underground floor will be made of concrete blocks of BS Klatovy. The internal staircase will be reinforced concrete. The elevator shaft across all floors will be fitted with an evacuation lift. The building will be insulated with a certified ETICS thermal insulation system.
Hotel in Giant
Keywords: Novostavba; hotel; restaurace; podsklepení; sedlová střecha; vikýř; svažitý terén; zděný; porotherm; BS Klatovy; Tondach; ETICS; diplomová práce; krov; projektová dokumentace; New build; hotel; restaurant; cellar; saddle roof; dormer; sloping terrain; brick building; porotherm; BS Klatovy; Tondach; ETICS; master´s thesis; roof trusses; project documentation